Foreing Partner Selection Criteria with the Example of Polish Importers and Exporters - Danik, Lidia (Studia Oeconomica Posnaniensia, 2017)
The paper presents the results of a study on the foreign partner selection criteria applied by Polish firms cooperating with partners from Germany and China. The analysis was conducted on a sample of 278 Polish exporters and importers. The study has shown, that the partner's interest in the cooperation and price the partner is willing to pay (in the case of exporters), the price offered (in the case of imports from China), partner's experience and the comprehensiveness of the offer (in the case of imports from Germany) are factors that influence the partner selection decision the most. Only a small dependence between the selection criteria and the partner's country of origin was observed. Some partner selection criteria were positively correlated with international cooperation experience indicators (years of international cooperation, number of countries the partners were coming from, number of partners in China/Germany).